How do you simplify the expression 2 - 8(-7 + x)+ 5x28(7+x)+5x?

2 Answers
Apr 6, 2018

58-3x583x

Explanation:

2-8(-7+x)+5x28(7+x)+5x

=2+56-8x+5x=2+568x+5x expand brackets

=58-3x=583x collect like terms

Apr 6, 2018

-3x + 583x+58

Explanation:

First, we use the distributive property to multiply/expand -8(-7+x)8(7+x):
-8 * -7 = 5687=56
-8 * x = -8x8x=8x

Now let's put that back into the expression:
2 + 56 - 8x + 5x2+568x+5x

Now we can simplify by combining like terms:
58 - 3x583x

We usually write expressions with the variable first, so I'm going to rewrite it that way:
-3x + 583x+58

Hope this helps!